Reading and academic performance of first and second English language grade 8 learners. - Krishnan, Khatpagam (My University, 2009)
Ten years into a democratic South Africa, significant changes have been witnessed in economic, social, political and educational development. Changes in the education system have resulted in many of the learners being encouraged to attend English medium schools although this is not their L1. Hence, there has been an increase of learners learning to read in a language that is not their first language. The transition from their home language to the language of learning is often not easy and impacts on their academic proficiency as well as academic development. This study investigated English reading abilities and academic performance of Grade 8 L1 and L2 learners attending an Ex-Model C school. The SDRT – Brown Level was used to assess the level of reading and its impact on academic achievement was investigated. Results show that the SDRT was highly correlated with, and a significant predictor of academic performance with certain tests being stronger predictors than others for L1 and L2 learners. Implications of these findings for the education of L1 and L2 learners are discussed.
Keywords: SDRT-Stanford Diagnostic reading test; L1-English first language; L2-English second language